Improving Students’ Reading Comprehension of English for Specific Purposes (ESP) at UKI Paulus Makassar - Luana Sasabone; Fien Pongpalilu (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
The achievement of learning Accounting English by using a special approach or ESP (English for Specific Purposes) in Accounting Study Program can often be said to be less than satisfactory. Many alumni even though they already master the field of science and profession so well in the field of accounting but in terms of communicate in English in their field of work, it can be said still very less. One indication of the cause, among others, is not optimal learning planning where the material provided is often not in accordance with the field of science taught by accounting students. This study aims to improve the students’ reading comprehension of English for specific purposes (ESP) at UKI Paulus Makassar. The subject of study was the students of accounting study program with the total number was 26 students. The result of study showed that The most significant improvement in reading comprehension is achieved which had the lowest scores on the cycle I in ESP test, the highest ones on the cycle II in ESP test. As conclusion this can improve the students’ reading comprehension of English for specific purposes (ESP) at UKI Paulus Makassar.